2018
DOI: 10.1002/cncr.31535
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel salivary gland cancer lymph node staging system

Abstract: Quantitative LN burden is an important determinant of survival in patients with SGC. Use of this variable may improve SGC staging. Cancer 2018. © 2018 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 34 publications
(47 reference statements)
7
45
0
Order By: Relevance
“…Hong et al, in a cohort of 87 patients with high-grade salivary gland cancer, found that ENE independently affected only DFS. [15] Aro et al [17] and Hsieh et al [37] demonstrated that ENE did not have any impact on survival. It is worth mentioning, however, that a recent report did identify ENE as one of the most important prognostic predictors [18].…”
Section: Extra-nodal Extensionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hong et al, in a cohort of 87 patients with high-grade salivary gland cancer, found that ENE independently affected only DFS. [15] Aro et al [17] and Hsieh et al [37] demonstrated that ENE did not have any impact on survival. It is worth mentioning, however, that a recent report did identify ENE as one of the most important prognostic predictors [18].…”
Section: Extra-nodal Extensionmentioning
confidence: 99%
“…Finally, the prognostic relevance of nodal dimensions and extranodal extension (ENE) are probably the most important nodal predictors in upper aerodigestive tract SCC, yet their significance in MSG carcinoma is less clear [9,[15][16][17][18]. In MSG carcinoma, the nodal disease burden, defined by nodal ratio (NR) and/or number of lymph-nodes involved, may have a more significant prognostic relevance [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…38 We suggest ND for all those who have a cytology class of IV or V, or clinical signs of malignancy, although in some cases, for example, with ACC, 39 Each metastatic lymph node on the neck up to four confers a 34% increased risk of salivary gland cancer mortality. 40 Still, the current tumor staging systems do not account for the absolute number of metastatic lymph nodes in salivary gland cancer, which might influence adjuvant treatment recommendations. Adjuvant RT is commonly recommended in high-grade malignancies, and postoperative RT/CRT was given in this series for 7 (44%) patients who had metastatic disease and/or a high-grade tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Each metastatic lymph node on the neck up to four confers a 34% increased risk of salivary gland cancer mortality 40 . Still, the current tumor staging systems do not account for the absolute number of metastatic lymph nodes in salivary gland cancer, which might influence adjuvant treatment recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Salivary gland tumors are associated with a high mortality rate, which may be attributed by the fact that they are more prone to metastasize to distant sites compared with other head and neck cancers (2). The rate of metastasis is 20-28% for submandibular and >90% for sublingual gland tumors (2)(3)(4). It has been reported that regional and distant metastasis of salivary gland cancer are important prognostic indicators for survival post-treatment (5).…”
Section: Introductionmentioning
confidence: 99%